FRI0170 The Comparative Effectiveness of Five Biologics as Second-Line Use for Patients with Rheumatoid Arthritis in Daily Clinical Practice. (9th June 2015) - Saito, K.; Nakano, K.; Nakayamada, S.; Hirata, S.; Kubo, S.; Fukuyo, S.; Miyagawa, I.; Sawamukai, N.; Hanami, K.; Tanaka, Y.
Abstract : Background: Since the approval of infliximab (IFX) in 2003, 7 biologics have been approved for rheumatoid arthritis (RA) in Japan. However, little is known regarding what to do when patients have an inadequate response to first biologics in daily clinical practice. Objectives: This study aimed to compare the effectiveness of tumor necrosis factor inhibitors (TNFi), tocilizumab (TCZ), abatacept (ABA) in RA patients with prior biologics use in daily clinical practice. Methods: We retrospectively examined 1713 patients who were treated with biologics (as 1st 1178, 2nd 409) between June 2008 and December 2014. We compared the effectiveness of IFX, etanercept (ETN), adalimumab (ADA), TCZ, ABA as 2nd-line use and switching from 1st TNFi to 2nd TNFi, TCZ, ABA based on retention rates and change in disease activity such as ΔCDAI(0-52W), ΔSDAI(0-52W), ΔDAS28-ESR(0-52W) (LOCF). Propensity score (PS) were generated using multinomial logistic regression and the study groups were matched regarding baseline variables including age, disease duration, disease activity, concomitant use of MTX and PSL. Results: Patients were treated with IFX19, ETN54, ADA89, TCZ122, ABA79, as 2nd biologics. Patients with a short disease duration, high titers of ESR, CRP and MMP-3 were treated with TCZ, and ETN was chosen for elderly patients. The retention rates at 52W were IFX44%, ETN58%, ADA55%, TCZ68%, ABA52%. A marked improvement of DAS28-ESR was observed in TCZ group among 5 biologics (p<0.01) and SDAI remission (REM) rates after 52W were IFX39%, ADA40%, TCZ26%, ABT29%. The rates of achieving SDAI REM were declined in the case of 2nd-line use of ETN16% compared to first-line use (Fig 1 ). Bio-free REM rates were IFX17%, ADA8%, ABT 6% even in 2nd-line use. In terms of switching of biologics, better treatment outcomes of ΔSDAI, ΔDAS28-ESR were observed in order of TNFi-TCZ (n=105) > TNFi-TNFi (n=133) = TNFi-ABA (n=58) as shown in Fig 2 . After PS-matching, switching to TCZ was still superior to other switching in ΔDAS28-ESR but not in ΔCDAI(0-52W). Conclusions: Our results suggest that TCZ bring about better improvements for the patients who showed an inadequate response to first biologics. After adjustment using PS-score matching, RA patients with prior anti-TNF exposures had similar outcomes if they switched to a new TNFi as compared with initiation of ABA. Disclosure of Interest: K. Saito: None declared, K. Nakano: None declared, S. Nakayamada: None declared, S. Hirata Consultant for: bureau from Abbvie, Bristol-Myers Squibb, Speakers bureau: bureau from Abbvie, Bristol-Myers Squibb, S. Kubo: None declared, S. Fukuyo: None declared, I. Miyagawa: None declared, N. Sawamukai: None declared, K. Hanami: None declared, Y. Tanaka Grant/research support from: Mitsubishi-Tanabe, Chugai, MSD, Astellas, Novartis, Speakers bureau: Abbvie, Chugai, Astellas, Takeda, Santen, Mitsubishi-Tanabe, Pfizer, Janssen, Eisai, Daiichi-Sankyo, UCB, GlaxoSmithKline, Bristol-Myers